2010
DOI: 10.1016/j.jjcc.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in mitral valve prolapse—Diagnosis and management

Abstract: Although mitral valve prolapse as a disease entity has been recognized for over 50 years, its precise definition has been elusive. Initial reports based the diagnosis on auscultatory findings (late systolic click - murmur), with left ventricular angiography as a confirmative test. Echocardiography, first the M-mode, and subsequently the two-dimensional, became the dominant diagnostic modality. However, the early reports did not distinguish between billowing valve and flail valve. The advent of surgical repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…1C) has been described. 18 Human MMVD causes prolapse or billowing of mitral valve leaflets into the left atrium during systole. The prevalence of MMVD in the human population is associated with age.…”
Section: Introductionmentioning
confidence: 99%
“…1C) has been described. 18 Human MMVD causes prolapse or billowing of mitral valve leaflets into the left atrium during systole. The prevalence of MMVD in the human population is associated with age.…”
Section: Introductionmentioning
confidence: 99%
“…According to clinical studies and medical research, a couple of causes have been identified as etiology of MVP, including degenerative (myxomatous) valve, fibroelastic deficiency, acute rheumatic valve disease, Marfan's syndrome, bacterial endocarditis, papillary muscle rupture and acute ischemia [3]. Moreover, myxomatous degeneration and fibroelastic deficiency account for most of MVP.…”
Section: Prevalence and Etiologymentioning
confidence: 99%
“…The former may present as a genetic disorder while the latter might be caused as an accelerated aging process. Furthermore, flail leaflet(s) of MVP has been found in more than 50% of myxomatous valves with ruptured chordate [3,4].…”
Section: Prevalence and Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…94 In advanced stages of MVP, mitral regurgitation (MR) occurs with a high possibility of heart failure. In fact, according to epidemiological studies, MR is the most common HVD.…”
Section: Mitral Valve Prolapsementioning
confidence: 99%